Development of maximum sprinting speed - Dick, F. W. (Track Technique, 1989)
The 15th Annual Congress of the European Athletics Coaches Association (held in East Germany last January) focused on sprints and hurdles. We are fortunate to have this contribution from EACA president and British director of coaching Frank Dick. Dick analyzes the Seoul 100m results and points out the important differences in sprint technique and training between men and women.